THE EFFECT OF SUBSIDIES ON INCOME INEQUALITY IN INDONESIA - Nugraha, Kunta (RIEBS, 2013)
It is generally accepted that one of the governmentâs responsibilities is to reduce income inequality. The most direct and easiest way to support poor people and stabilise prices is through subsidies. There are subsidies for energy and, for instance, for agricultural fertilisers, food and public utilities. Since 1998 in Indonesia, subsidies have tended to increase, especially energy subsidies (fuel and electricity). This paper used benefit incidence analysis, which allocates the benefits of subsidies to households from the poorest to the richest income groups. The major data used were from 2008 National Socioeconomic Survey (Susenas). This research was an important contribution to strengthening the literature on subsidies and income inequality in Indonesia. An important finding was that subsidies benefited the highest income households more than the lowest income households, even though subsidies reduced income inequality. The percentage of subsidy benefits to the lowest income group was higher than for the richest. In the long run, subsidy programs that favour the higher income households can worsen income inequality if the consumption of subsidised goods by high-income households increases gradually. I suggest that if the aim is at reducing income inequality, subsidies, other than those for energy, need to be increased and the subsidy system need to be improved by moving from price subsidies to targeted subsidies.